IDENTIFIKASI SPESIES RAYAP PADA ZONA REFERENSI DAN ZONA REHABILITASI TAMAN NASIONAL MERU BETIRI - Chuck Nuris Alvinda; Wahcju Subchan; Jekti Prihatin (saintifika, 2017)
Meru Betiri National park has a region part, it’s reference zone and rehabilitation zone. Referensi zone is a conservation area that have to protect from damage by human interference to protect flora, fauna and other environmental component for importance of next generation. Rehabilitation zone was damaged without original vegetation and be a seasonal land farm. Termites is a important part of insect in material recycling of plant trhough disintegration process. The aim of the research are to knowing types of termites and to knowing the different of termites diversity in referensi zone and rehabilitation zone Meru Betiri National Park. Research methods by used direct sampling. The result of research has get 2 species founded, that’s Macrotermes gilvus Hagen (mayor), Macrotermes gilvus Hagen (minor) and Nasutitermes metangensis with totally 194 individual. Index of species diversity (H’) in the reference zone = 0, it's caused there are only one species founded and index of species diversity (H’) in rehabilitation zone = 1,036. It can be concluded that diversity of species on both has a different level diversity although same on low diversity.